Beyond Taharah: Integrative Interpretation of QS Al-Baqarah 2:222 in Biology, Psychology, Spirituality - Putri Yasmin Nurul Azizah Tandean; Jihan Kharisma Hidayatulloh; Ahmad Nurrohim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
QS. Al-Baqarah [2]: 222 discusses menstruation through the concept of adha, the prohibition of sexual intercourse, and regulations of cleanliness until a state of purity is attained. In the classical exegesis of al-Qurtubi, this verse is understood within the normative-legal framework of fiqh al-taharah, thereby confining its meaning predominantly to ritual jurisprudential rulings. Such an approach reveals limitations in interpreting menstruation as a multidimensional phenomenon that also encompasses biological and psychological aspects. This study is a library-based research employing an integrative thematic exegesis approach, combining linguistic analysis, al-Qurtubi’s tafsir, and relevant biological and psychological literature. The findings indicate that adha refers to biological disruption and physical-emotional discomfort, rather than merely “impurity”. The phrase fa’tazilu is also understood as a protective restriction of sexual relations, rather than social isolation. The integrative analysis demonstrates that menstruation represents the unity of physiological, psychological, and spiritual dimensions. Thus, the verse is not solely normative-legal in nature, but also contains protective, relational, and reflective meanings in understanding women’s bodily experience in a more holistic manner